Influence of current density and mechanical agitation on the electrodeposition process of Zn-Ni alloys (Research, Society and Development, 2020)
The effects of current density and mechanical agitation of the bath in the electrodeposition process to obtain the Zn-Ni alloy were evaluated. An electrolytic bath was used consisted of nickel sulfate, zinc sulfate, sodium sulfate, boric acid and sodium citrate at pH 7.0. The current density was evaluated in the range of 10-50 mA / cm², and, for mechanical agitation, it was evaluated in the range of 30-70 rpm. As optimization tool, a complete 2² factorial design was used with three central elements associated with the Response Surface Methodology (RSM). It was observed that the increase in current density and in mechanical agitation caused an increase in the atomic percentage of nickel in the coatings. The percentage of zinc increased with decreasing current density. The optimum nickel value obtained was 39 at.%. The electrodeposition was anomalous. The microhardness increased with the increase in the percentage of nickel and with the decrease in the percentage of Zn in the coating. The coatings showed nodules on the surface with different sizes and shapes.